Pengaruh Penerapan Good Governance, Pengawasan Intern Dan Disiplin Kerja Terhadap Kinerja Pemerintah Daerah Kota Pekanbaru - Dina Epriliani (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
that affect the performance of local governments. The method used in this research is a questionnaire. The population used in this study were local government employees of the city of Pekanbaru and 395 samples. The data analysis technique used is the test instrument, namely validity, This study aims to examine the implementation of good governance, internal supervision, and reliability, classical assumption test, namely normality, heteroscedasticity and multicollinearity, f test, t test, multiple linear regression analysis and coefficient of determination test. The types and techniques of data collection used are primary data obtained directly from respondents. The results of the study simultaneously see the application of good governance, internal supervision and work discipline simultaneously affect the performance of local governments. the implementation of good governance, internal supervision and work discipline are one of the indicators that affect the performance of local governments Keywords: Implementation of good work discipline governance ; internal supervision ; work discipline